Examining the Impact and School‐Level Predictors of Impact Variability of an 8th Grade Reading Intervention on At‐Risk Students' Reading Achievement. Issue 1 (7th February 2018) - Fien, Hank; Anderson, Daniel; Nelson, Nancy J.; Kennedy, Patrick; Baker, Scott K.; Stoolmiller, Michael
Abstract: The purpose of the present article is to report on a large‐scale investigation of six school districts' implementation of an initiative aimed at reducing dropout rates by improving reading achievement in the middle grades. Data for the Middle School Intervention Project (MSIP) were collected in 25 middle schools across the state of Oregon. We examined (a) the degree to which the schools improved reading achievement for struggling readers in 8th grade, and (b) whether we could account for school differences in the treatment effect through measured explicit and intensive intervention factors. At the end of 8th grade there was no evidence of significant or positive effects on the two primary reading outcome measures.